ChemInform Abstract: Access to 2, 3‐Disubstituted Benzofurans Through One‐Pot Acid‐Catalyzed Nucleophilic Substitution/TBAF‐Mediated Oxacycloisomerization. Issue 9 (5th March 2013) - Reddy, Chada Raji; Krishna, Gaddam; Kavitha, Nerella; Latha, Bellamkonda; Shin, Dong‐Soo
Abstract A mild, efficient and metal‐free synthesis of benzofurans.